What AI Apps Can Monitor My Health? A Professional and Academic Overview - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
What AI Apps Can Monitor My Health? A Professional and Academic Overview The integration of Artificial Intelligence (AI) into mobile health (mHealth) ap...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics